Mafic-ultramafic intrusions of Matokulma, Palojärvi, and Hongonniittu within the Central Finland Granitoid Complex with special reference to their petrogenesis and ore potential - Seppo Karvinen; Hannu V. Makkonen; Perttu Mikkola; O. Tapani Rämö; Hannu Huhma; Matti Niskanen (Bulletin of the Geological Society of Finland)
We describe three previously unknown or poorly studied mafic-ultramafic intrusions (Matokulma, Palojärvi, Hongonniittu) from the south-central part of the Paleoproterozoic Central Finland Granitoid Complex (CFGC). The ore potential and petrogenesis of the intrusions, with the focus on Matokulma and Palojärvi, are discussed based on petrography and geochemistry and, possible relationships with the Ni-Cu ore potential Vammala–Kotalahti type intrusions are examined. The poorly exposed Hongonniittu intrusion is likely genetically related to the Palojärvi intrusion. Median Mg-numbers for Matokulma and Palojärvi are 72 and 49, respectively. They consist of cumulus clinopyroxene, orthopyroxene and plagioclase, in case of Palojärvi also Fe-Ti oxide, and oikocrystic magmatic amphibole enclosing the cumulus phases. In Matokulma, mafic dikes cut the surrounding granitoids. A late leucogabbro dike with a U-Pb zircon age of 1882 ± 5 Ma constrains the minimum age for the Palojärvi intrusion. The Palojärvi leucogabbro has relatively radiogenic Nd isotope composition and is, in this respect, similar to Kotalahti-type mafic-ultramafic intrusions farther northeast. The parental magmas of the Matokulma and Palojärvi intrusions contained approximately 4–6 wt.% and 2–4 wt.% MgO, respectively. Magmatic amphibole, enrichment in large ion lithophile elements (LILE) and depletion in high field strength elements (HFSE) indicate crystallization from hydrous, evolved basaltic magmas. Owing to their evolved nature, the intrusions are not potential for magmatic Ni-Cu mineralizations, but Palojärvi could potentially host a Fe-Ti-V mineralization in deeper, concealed parts of the intrusion.